Duolingo Dominance in Mobile-Assisted Language Learning: A Survey of User Preferences, Skill Targets, and Device Trends - Falahi, Kamil (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2025)
The proliferation of mobile technology has transformed foreign language learning, offering flexible solutions for learners with time or accessibility constraints. This study investigates user preferences for mobile applications in language acquisition, examining application choices, targeted language skills, usage frequency, and device accessibility. Through a quantitative survey of 75 learners (aged 13–60) across Indonesia, results reveal that 84% leverage mobile apps for language learning, with Duolingo emerging as the dominant platform (67.6%). Participants primarily aimed to improve all core language skills (66.6%), engaged daily (41.2%), and dedicated 15–30 minutes per session (44.4%). Smartphones were the preferred access point (52.3%), particularly among working professionals (62.6% of respondents). The findings highlight mobile apps as critical tools for democratizing language education and underscore the need for enhanced speaking-focused features in future designs